2012
DOI: 10.1007/s11255-012-0123-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple brown tumors causing spinal cord compression in association with secondary hyperparathyroidism

Abstract: Differential diagnosis of sudden neurologic deficits and paraplegia in renal patients with secondary HPPT must consider the possibility of brown tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…the Non-anemia group (P = 0.005), suggesting that the influence of physical symptoms and mental symptoms on everyday life was greater in the Anemia group than in the Non-anemia group. Secondary hyperparathyroidism is one of the most important complications in HD patients (13)(14). Severe SHPT can also decrease QOL by causing symptoms of bone pain (13), muscle weakness (14), and itching (15).…”
Section: Validity Of a Checklist For Hd Patients 479mentioning
confidence: 99%
See 1 more Smart Citation
“…the Non-anemia group (P = 0.005), suggesting that the influence of physical symptoms and mental symptoms on everyday life was greater in the Anemia group than in the Non-anemia group. Secondary hyperparathyroidism is one of the most important complications in HD patients (13)(14). Severe SHPT can also decrease QOL by causing symptoms of bone pain (13), muscle weakness (14), and itching (15).…”
Section: Validity Of a Checklist For Hd Patients 479mentioning
confidence: 99%
“…Secondary hyperparathyroidism is one of the most important complications in HD patients (13)(14). Severe SHPT can also decrease QOL by causing symptoms of bone pain (13), muscle weakness (14), and itching (15). Malindretos et al reported that SHPT appears to be associated with poor pain component summary scores and physical component summary scores (16).…”
Section: Validity Of a Checklist For Hd Patients 479mentioning
confidence: 99%
“…The brown tumor is recognized as a non-neoplastic bone reactive process due to increased osteoclastic activity and localized fibroblast proliferation. [1][2][3][4][5][6][7][9][10][11][12][13][14] Its name derives from its reddish brown appearance, due to microhemorrhages and hemosiderin deposition. [1][2][3][4][5] The IRC secondary hyperparathyroidism results from injury of calcitriol (1,25dihydroxyvitamin D3) synthesis, leading to hypocalcemia and phosphate retention and increased production of parathyroid hormone, which can lead to the development of brown tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Brown tumor, or osteoclastoma, is a benign bone injury, which occurs only in the presence of primary or secondary hyperparathyroidism, with increased incidence in the presence of primary hyperparathyroidism. [1][2][3][4][5][6] Even though infrequent, the relationship of brown tumor with secondary hyperparathyroidism is well established. [1][2][3][4][5][6] Palavras-chave ► hiperparatireoidismo secundário ► compressão da medula espinhal ► tumor de células gigantes do osso…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation